Enhancement of the chromium removal behavior of Moringa oleifera activated carbon by chitosan and iron oxide nanoparticles from water. (1st January 2021) - Bahador, Farahnaz; Foroutan, Rauf; Esmaeili, Hossein; Ramavandi, Bahman
Highlights: An activated carbon (AC) was produced from Moringa oleifera tree. Chitosan (CS) and Fe3 O4 were used to enhance the chromium removal by AC. The majority of Cr(VI) was removed by CS/AC/Fe3 O4 at pH2 and 50 min contact time. CS/AC/Fe3 O4 magnetic adsorber was recycled 5 times with an efficiency of >90 %. Abstract: The effect of chitosan and Fe3 O4 magnetic nanoparticles on the chromium adsorption property of Moringa oleifera activated carbon (AC) was explored. Various techniques were applied to reveal the properties of adsorbers to absorb chromium ions. A majority of the pollutant was removed at pH2 and 50 min. The kinetic behavior of the chromium uptake process was governed by the pseudo-second-order kinetic model (PSOKM). Based on the thermodynamic investigation, the chromium adsorption using all adsorbers was exothermic and spontaneous. The maximum single-layer adsorption capacity of AC, CS/AC, AC/Fe3 O4, and CS/AC/Fe3 O4 adsorbers was 56.78 mg/g, 114.80 mg/g, 121.70 mg/g, and 130.80 mg/g, respectively. The isotherm constants quantity highlighted that the Cr-adsorption process is optimal and physical. The acquired findings revealed that the modification of AC by chitosan and Fe3 O4 nanoparticles increased the Cr adsorption. Adsorbers re-used up to 5 stages with a yield >90 %, which indicates that the composites are a promising option for Cr removal.